Scientific investigations on Integral General Medicine during the historic evolution of this specialty. Cienfuegos, 1988-2005. - Margarita Roméu Escobar; Beatriz Sabina Roméu; Pilar Almaguer Sabína; Gloria Lara Calderín (Medisur)
Background: The program of the doctor and nurse of the family has undergone several structural, organizational, methodological, of socioeconomic context and of political priority changes and it is unknown the influence of such evolution on the works of conclusion of the Integral General Medicine specialty in Cienfuegos. Objective: To compare the works of conclusion of the Integral General Medicine specialty in three different stages of the program of the doctor and nurse of the family in Cienfuegos. Methods: A descriptive study for which a sample of the act of the pertaining to the estate exams, archived in the Faculty of Medical Sciences of Cienfuegos, was revised, corresponding to the years 88-92, 99-00, 04-05, and tribunal members of the exams were enquired to know about the work situation of the authors, tutors, grades, investigation themes. Results: It was found that the authors work situation varies according to the municipalitie´s expansion. The present stage is characterized by the location in Venezuela and Haiti. Specialists of the Health Primary Attention have tutored most of the investigations. The excellent grade was given to more than 50% of the investigations in the first and last stage. Conclusions: The majority of the investigations topics correspond to the main Health programs, but new ones are being adopted while others are abandoned. Methodological deficiencies continue.